2020
DOI: 10.3390/jcm9051465
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Submucosal Dissection of Papillary Gastric Adenocarcinoma; Systematic Review

Abstract: This study evaluated the possibility of endoscopic submucosal dissection (ESD) for early gastric cancer with papillary adenocarcinoma (EGC-PAC). PAC, an uncommon pathologic type of stomach cancer, is classified into differentiated-type histology. However, aggressive features, including a high rate of submucosal invasion, lymphovascular invasion (LVI), and lymph node metastasis (LNM), have been reported in studies with surgical specimens. Treatment outcomes of ESD for EGC-PAC have not been precisely demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In a review analyzing 15 studies, en bloc resection, complete resection, and curative resection rates were 89.7% (95% CI, 55.3% to 98.4%), 85.3% (95% CI, 67.7% to 94.2%), and 67% (95% CI, 43% to 84.5%), respectively, and there was no LN metastasis in curative resection patients. 20 In another study that analyzed the ESD results of 87 patients with papillary-type EGC, patients who underwent curative resection were followed up for a median of 58 months, and no extragastric recurrence was observed. 21 In this study, the en bloc resection and curative resection rates were 91.8% and 86.6%, respectively, and 91.1% and 93.7%, respectively, in the case of mucosal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In a review analyzing 15 studies, en bloc resection, complete resection, and curative resection rates were 89.7% (95% CI, 55.3% to 98.4%), 85.3% (95% CI, 67.7% to 94.2%), and 67% (95% CI, 43% to 84.5%), respectively, and there was no LN metastasis in curative resection patients. 20 In another study that analyzed the ESD results of 87 patients with papillary-type EGC, patients who underwent curative resection were followed up for a median of 58 months, and no extragastric recurrence was observed. 21 In this study, the en bloc resection and curative resection rates were 91.8% and 86.6%, respectively, and 91.1% and 93.7%, respectively, in the case of mucosal cancer.…”
Section: Discussionmentioning
confidence: 99%
“… 5 A recent systemic review including 15 studies also showed that submucosal invasion and LVI were frequent in EGC-P, and the curative resection rate was only 67.0% (95% confidence interval, 43.0% to 84.5%). 6 Accordingly, ESD should be more carefully applied for EGC-P than for EGC with other differentiated-type histologies.…”
mentioning
confidence: 99%
“…11 Therefore, the characterization of lymph nodes could represent the main target of EUS during EGC staging rather than the T parameter, especially for P-EGC.Several studies performed on surgical specimens reported a worse prognosis associated with P-EGC than with other differentiated types. 2,12 However, the treatment outcomes of ESD for P-EGC have not been precisely documented. 12 A recent Korean study 13 evaluated the short-and long-term outcomes after ESD in P-EGC; the curative resection rate of P-ECG was significantly lower than those of well differentiated and moderately differentiated EGC (49.4% vs 72.5% and 93.7%, respectively), although it increased to 72.5% for mucosal (T1a) cancer.…”
mentioning
confidence: 99%
“…2,12 However, the treatment outcomes of ESD for P-EGC have not been precisely documented. 12 A recent Korean study 13 evaluated the short-and long-term outcomes after ESD in P-EGC; the curative resection rate of P-ECG was significantly lower than those of well differentiated and moderately differentiated EGC (49.4% vs 72.5% and 93.7%, respectively), although it increased to 72.5% for mucosal (T1a) cancer. Despite the poor short-term outcomes, the long-term outcomes of ESD for P-EGC were favorable once…”
mentioning
confidence: 99%
See 1 more Smart Citation